2000
DOI: 10.1002/pen.11345
|View full text |Cite
|
Sign up to set email alerts
|

Foaming of PS/wood fiber composites using moisture as a blowing agent

Abstract: This paper presents an experimental study on foam processing of polystyrene (PS) and high‐impact polystyrene HIPS/wood‐fiber composites in extrusion using moisture as a blowing agent. Wood‐fiber inherently contains moisture that can potentially be used as a blowing agent. Undried wood‐fiber was processed together with PS and HIPS materials in extrusion and wood‐fiber composite foams were produced. The cellular morphology and volume expansion ratios of the foamed composites were characterized. Because of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 19 publications
2
110
0
1
Order By: Relevance
“…URING THE LAST decade, extensive efforts have been made on the use of wood fibers as fillers or reinforcers for thermoplastic matrices [1][2][3][4][5][6][7][8][9][10][11]. The rationale behind these efforts is that wood fibers offer many advantages over the most commonly used inorganic materials including a lower cost on a volumetric basis, higher specific strength and modulus, flexibility during processing, etc.…”
Section: Introduction Dmentioning
confidence: 99%
“…URING THE LAST decade, extensive efforts have been made on the use of wood fibers as fillers or reinforcers for thermoplastic matrices [1][2][3][4][5][6][7][8][9][10][11]. The rationale behind these efforts is that wood fibers offer many advantages over the most commonly used inorganic materials including a lower cost on a volumetric basis, higher specific strength and modulus, flexibility during processing, etc.…”
Section: Introduction Dmentioning
confidence: 99%
“…45,46 It has been confirmed by studies that volatile extractives are present in natural fiber 40,47,48 and they are responsible for decrease of mechanical property of the compound. 27,42,45,47,49 Yosomiya argued that poor adhesion of a material is due to presence of low surface tension material such as impurities or adsorbed water layers. 50 This leads to interfacial de-wetting between fiber surface and polymer matrix.…”
Section: 폴리머 제39권 제1호 2015년mentioning
confidence: 58%
“…After all, natural fi ber-fi lled polymer composites commonly have high densities. Therefore, the composites can be foamed to lessen their density using chemical or physical blowing agents (Rizvi et al, 2000). Natural fi ller reinforced composites have shown excellent performance regarding physical, mechanical and thermal properties (Ozen et al, 2013; Kiziltas et al, 2014).…”
Section: Introduction To Wood Plastic Composite Technology 1 Uvod U mentioning
confidence: 99%
“…Polystyrene/wood foamed composites were studied by Rizvi et al, (2000), who used hydrocerol compounds and wood particle water (moisture content of 8 %) at 130 °C and 140 °C. These results have shown that expansion ratio was 9 to 20 %.…”
Section: Characteristic Properties Ofmentioning
confidence: 99%
See 1 more Smart Citation